Sports massage as a method of preventing delayed onest muscle soreness - Paweł Choroszewicz; Anna Maria Dobosiewicz; Nataliia Badiuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Physical activity, despite it's many advantages for health and fitness, can have negative effects on humans. One of them may be delayed muscle soreness (DOMS), which appears 48-72 hours after the end of training. People performing intensive training, performing eccentric exercises, as well as people who take up activity once in a while are exposed. DOMS can meet both qualified athletes and amateurs of sport. There is a collage of hypotheses explaining the formation of delayed muscle soreness. The most recent one is that DOMS is the result of muscle micro-injuries. There is also no single effective method of pain treatment. Pharmacology, hot and cold treatment methods, stretching and massage are applied. Research on athletes as well as amateur athletes shows that sports massage leads to faster regeneration of muscles affected by DOMS.